PENGEMBANGAN LKPD INTERAKTIF BERBANTUAN APLIKASI WEBSITE WORDWALL PADA PEMBELAJARAN BAHASA INDONESIA ELEMEN MEMBACA PEMAHAMAN KELAS V SEKOLAH DASAR - Deli Puspita Anjami; Muhammadi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research was motivated by the low use of digital media in learning at elementary schools. The purpose of this study was to develop an Interactive LKPD assisted by the Wordwall website application in Indonesian language learning for fifth grade elementary school students. The research problems were obtained from observations and interviews conducted in several schools, namely SD Negeri 16 Pagambiran, SD Negeri 25 Pagambiran, and SD Negeri 35 Pagambiran. The results of the observations showed that teachers and students were still not optimal in utilizing digital technology in the learning process. This condition caused low student participation, learning interest, and learning outcomes in Indonesian language learning. This study used a Research and Development (R&D) approach with the ADDIE model consisting of five stages, namely Analysis, Design, Development, Implementation, and Evaluation. The data collected included validity, practicality, and effectiveness data. The results showed that the developed Interactive LKPD had a very good validity level with percentages of 96% from material experts, 81% from language experts, and 93% from media experts. The practicality results showed percentages of 95% from teachers and 95.75% from students with a very practical category. In addition, the effectiveness results showed percentages of 85.71% in the trial school and 91.67% in the research school with a very effective category. Based on these results, it can be concluded that the Interactive LKPD assisted by the Wordwall website is appropriate to be used in Indonesian language learning for fifth grade elementary school students.